Neuroprotective Effect of 2-(Benzyloxy)arylureas Is Not Related to CypD Inhibition nor Suppression of mPTP Opening - Haleckova, Annamaria; Syrova, Veronika; Joklova, Andrea; Vernerova, Tereza; Hurdalek, Jan; Endlicher, Rene; Salamonova, Katerina; Bubelova, Petra; Febda Kurnia, Haka Fajriana; Schmidt, Monika; Musilek, Kamil; Zemanova, Lucie; et al. (ACS medicinal chemistry letters, 2024)
Cyclophilin D (CypD) is a mitochondrial enzyme widely accepted as a regulator of the mitochondrial permeability transition pore (mPTP). Excessive opening of mPTP is associated with mitochondrial dysfunction and the development of various diseases; thus, suppression of mPTP opening through CypD inhibition presents a promising therapeutic approach. However, only a limited number of selective CypD inhibitors are currently available. In this study, 10 derivatives of 2-(benzyloxy)arylurea similar or identical to previously published CypD/mPTP inhibitors were synthesized. Unlike the original reports that assessed the opening of mPTP at the cellular level, the compounds were tested directly on the purified CypD enzyme to validate their putative mechanism of action. Additionally, the effect of the selected compounds was tested on isolated mitochondria. The obtained results show that the compounds are only weak inhibitors of CypD and mPTP opening, which is in contrast to previous conclusions drawn from the unspecific cellular JC-1 assay.